Comparison of low attenuation areas on computed tomographic scans between inner and outer segments of the lung in patients with chronic obstructive pulmonary disease: incidence and contribution to lung function. Issue 5 (1st May 1999) - Nakano, Y; Sakai, H; Muro, S; Hirai, T; Oku, Y; Nishimura, K; Mishima, M
Abstract : BACKGROUND: The low attenuation areas on computed tomographic (CT) scans have been reported to represent emphysematous changes of the lung. However, the regional distribution of emphysema between the inner and outer segments of the lung has not been adequately studied. In this study the regional distribution of low attenuation areas has been compared by quantitative CT analysis and the contribution of the regional distribution to pulmonary function tests evaluated in patients with chronic obstructive pulmonary disease (COPD). METHODS: Chest CT images and the results of pulmonary function tests were obtained from 73 patients with COPD. The lung images were divided into inner and outer segments in the upper (cranial), middle, and lower (caudal) sections. The percentage ratio of low attenuation area to corresponding lung area (LAA%) was then calculated. The LAA% of each segment was also compared with the results of pulmonary function tests. RESULTS: The mean (SD) LAA% of the inner segment was 39.1 (18.5) compared with 28.1 (13.2) for the outer segment (p<0.0001). Linear and multiple regression analyses revealed that airflow limitation is closely correlated with the inner segment LAA% of the lower lung. In contrast, the carbon monoxide transfer factor is closely correlated with the inner segment LAA% of the upper lung. CONCLUSION: Low attenuation areas on CT scans are more often found in the inner segment of the lung than in the outer segment, and the contribution of the inner segment to pulmonary function tests may be greater than the outer segment.